2014
DOI: 10.1590/s1679-62252014000100010
|View full text |Cite
|
Sign up to set email alerts
|

A new unicuspid-toothed species of HypostomusLacépède, 1803 (Siluriformes: Loricariidae) from the rio Paraguai basin

Abstract: A new unicuspid-toothed armored catfish species of Hypostomus is described from the Bodoquena Plateau, rio Paraguai basin, Mato Grosso do Sul State, Brazil. The new species is distinguished from its congeners, with exception of H. fonchii, by having unicuspid teeth (vs. bicuspid teeth); from H. fonchii it is distinguished by having median series of lateral plates with 26-27 (vs. 28); by lower number of premaxillary and dentary teeth (7-10 vs. 18-21; 8-13 vs. 18-25, respectively); for possessing more depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 863 publications
(8 citation statements)
references
References 20 publications
(14 reference statements)
0
6
0
2
Order By: Relevance
“…Hypostomus plecostomus (Linnaeus, 1758) was described with 2n = 54 chromosomes 48 . However, it was considered a misidentification case, once the recent cytogenetic studies in this species has demonstrated 2n = 68 chromosomes 49 [11][12][13]50 . The chromosomal data in this study showed that 2n = 68 and different karyotype formulae between H. commersoni and H. derbyi could be explained by pericentric inversions.…”
Section: Discussionmentioning
confidence: 99%
“…Hypostomus plecostomus (Linnaeus, 1758) was described with 2n = 54 chromosomes 48 . However, it was considered a misidentification case, once the recent cytogenetic studies in this species has demonstrated 2n = 68 chromosomes 49 [11][12][13]50 . The chromosomal data in this study showed that 2n = 68 and different karyotype formulae between H. commersoni and H. derbyi could be explained by pericentric inversions.…”
Section: Discussionmentioning
confidence: 99%
“…Hypostomus Lacépède is the most diverse genus of Loricariidae and it is currently composed of 132 valid species (Zawadzki & Hollanda Carvalho, ; Zawadzki et al , ). With regard to the cytogenetic contribution to the taxonomic and evolutionary understanding of Hypostomus , Artoni & Bertollo (, ) were pioneers in this field and their studies are widely cited as references on the subject.…”
Section: Nominal Revision and Karyotypic Characteristics Of Species Omentioning
confidence: 99%
“…Loricariidae is the family with the largest number of representatives of this order, which is popularly known as plecos or catfish. The genus Hypostomus is considered one of the most taxonomically complex of Neotropical ichthyofauna, which currently comprises 130 valid species (Zawadzki et al, 2014) showing great diversity in the morphology and color pattern and thereby making identification of certain species difficult .…”
Section: Introductionmentioning
confidence: 99%